Streptococcus agalactiae infection in zebrafish larvae. (February 2015) - Kim, Brandon J.; Hancock, Bryan M.; Del Cid, Natasha; Bermudez, Andres; Traver, David; Doran, Kelly S.
Abstract: Streptococcus agalactiae (Group B Streptococcus, GBS) is an encapsulated, Gram-positive bacterium that is a leading cause of neonatal pneumonia, sepsis and meningitis, and an emerging aquaculture pathogen. The zebrafish ( Danio rerio ) is a genetically tractable model vertebrate that has been used to analyze the pathogenesis of both aquatic and human bacterial pathogens. We have developed a larval zebrafish model of GBS infection to study bacterial and host factors that contribute to disease progression. GBS infection resulted in dose dependent larval death, and GBS serotype III, ST-17 strain was observed as the most virulent. Virulence was dependent on the presence of the GBS capsule, surface anchored lipoteichoic acid (LTA) and toxin production, as infection with GBS mutants lacking these factors resulted in little to no mortality. Additionally, interleukin-1β ( il1b ) and CXCL-8 ( cxcl8a ) were significantly induced following GBS infection compared to controls. We also visualized GBS outside the brain vasculature, suggesting GBS penetration into the brain during the course of infection. Our data demonstrate that zebrafish larvae are a valuable model organism to study GBS pathogenesis. Highlights: Zebrafish larvae model of Group B Streptococcus infection. Visualization of bacterial penetration of the blood brain barrier. Group B Streptococcus mutants are attenuated in the zebrafish larvae model of infection.